Prospects For Expanding The Export Capacity Of Small Businesses Of Uzbekistan On The Basis Of Wto Requirements In The International Trade System - Abdullayev, Akhrorjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the issues of expanding the export potential of small business entities in the context of Uzbekistan’s accession to the World Trade Organization (WTO). The country’s export volumes, the share of small and medium-sized businesses in foreign trade, and the opportunities and constraints arising from WTO requirements are covered based on numerical data. The analysis showed that WTO membership will accelerate Uzbekistan’s integration into international trade, create new market opportunities for small businesses, but will require increasing their competitiveness, standardization, and strengthening financial support systems. The article puts forward the necessary strategic directions and policy recommendations for the development of small business exports.